Abortion in a Progressive Legal Environment: The Need for Vigilance in Protecting and Promoting Access to Safe Abortion Services in South Africa - Trueman, Karen A. (American Public Health Association, 2013)
The importance of South Africa as a model for reproductive self-determination in Africa cannot be underestimated. Abortion has been legal since 1996, and the country has some of the most developed government systems for the provision of abortion care on the continent. Yet in the same way opponents of abortion in the United States have whittled away at access with increased bureaucracy, South Africa faces similar assaults that leave women without safe care and threaten to turn back achievements made during the past 16 years. I explore the history of the law, subsequent legal challenges, and new threats to women’s access to abortion services, including service delivery issues that may influence the future of public health in the country.